Assessment of aortic morphology and compliance in children and adolescents with Ullrich-Turner syndrome (UTS) using magnetic resonance imaging (MRI) - Kneppo, Carolin; Eichhorn, Joachim; Ley, Sebastian; Schenk, Jens-Peter; Gorenflo, Matthias; Bettendorf, Markus (The journal of pediatric endocrinology and metabolism, 2014)
Aim: The aim of this study was to evaluate the morphology and elastic properties of the aorta in children and adolescents with Ullrich-Turner syndrome (UTS) treated with growth hormone, by using magnetic resonance imaging (MRI). Methods: Thirty-seven conscious UTS patients were examined using a 1.5-T whole-body MRI. Contrast-free three-dimensional (3D)-MR angiographies were performed, including 2D cine MRI, to calculate the aortic compliance (C) and cine of the aortic valve. Results: Changes of aortic morphology were evident in 40% of the patients, whereas six had more than one alteration. A bicuspid aortic valve was identified in three patients that were missed by previous echocardiography. The aortic compliances in UTS patients were similar to those in healthy persons. Conclusion: This study shows that aortic morphology and compliance can be assessed by MRI without using contrast agents and without sedation in children and adolescents with UTS.